Susuan Dalam Tinjauan Tafsir Ayat-Ayat Ahkam - Ramadhona, Suci; Rafiqah, Lailan; Sumanto, Dedi; Zainuddin, Asriadi (Al-Mizan (e-Journal), 2023)
Breastfeeding is a bonding of a mother to her baby which is natural to meet the basic needs of the baby so that it can grow and develop physically and psychologically properly. Islamic teachings explicitly regulate this in the Qur'an and Hadith, which aim to make the basic life processes of a child follow Islamic law. This study aims to analyze breastfeeding (ar-radha'ah) problems, especially regarding breastfeeding of non-biological children which creates intimacy between mother and child, and contemporary problems related to breastfeeding through the verses of law in the Qur'an based on the opinion of scholars, especially commentators. The research in this paper uses qualitative methods with data collection techniques based on literature study by reading several references such as the Qur'an, hadith, books, and articles, and analyzing the opinions of commentators. The results of this study state that breastfeeding is recommended for mothers to their biological children, but breastfeeding is carried out by mothers to non-biological children, so this breastfeeding has legal implications, namely the prohibition of marriage. Breastfeeding creates friendship between mothers who donate breast milk and babies who are breastfed either through direct suction (tsadyu) or not, even if it's only one suck or by way of fair (sau'ut) which lasts for two years because this will form bones and grow flesh in the growth of the baby so that it will make marriage illegal. In ar-radha'ah include recommendations for breastfeeding, the father's obligation to provide support during breastfeeding, the permissibility of breastfeeding children other than the biological mother, and the nature of breastfeeding.